2013
DOI: 10.5194/acp-13-4697-2013
|View full text |Cite
|
Sign up to set email alerts
|

Role of external factors in the evolution of the ozone layer and stratospheric circulation in 21st century

Abstract: The chemistry-climate model (CCM) SOCOL has been used to evaluate the contributions of the main anthropogenic factors to the simulated changes of ozone and stratospheric dynamics during the 21st century. As the main anthropogenic factors we consider the atmospheric concentration of the greenhouse gases (GHG), ozone depleting substances (ODS) and sea surface temperature and sea ice (SST/SI). The latter is considered here as an independent factor because the majority of the CCMs prescribe its evolution. We have … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 29 publications
1
39
1
Order By: Relevance
“…Continued ozone observations and monitoring are needed to consolidate the evidence of ozone recovery and also further improve our understanding of the complex ozoneclimate feedback (in combination with chemistry-climate modeling) that will have a significant impact on future evolution of ozone (Fleming et al, 2011;Zubov et al, 2013;Pawson et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Continued ozone observations and monitoring are needed to consolidate the evidence of ozone recovery and also further improve our understanding of the complex ozoneclimate feedback (in combination with chemistry-climate modeling) that will have a significant impact on future evolution of ozone (Fleming et al, 2011;Zubov et al, 2013;Pawson et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Wave forcing depends on the mean state of the flow, and vice versa (Charney and Drazin, 1961;Holton and Mass, 1976); changes in either affect ozone transport by a change in the speed of the BDC that leads to adiabatic heating, or cooling, and directly affects chemistry through temperature-dependent reaction rates (Chen et al, 2003;García-Herrera et al, 2006;Shepherd et al, 2007;Lima et al, 2012). As such, ozone and temperature have an inverse relationship in the equatorial stratosphere above 10 hPa, which in turn has a dependence on dynamics (Fusco and Salby, 1999;Mäder et al, 2007;Stolarski et al, 2012), although this is not always the case in the lower stratosphere (Zubov et al, 2013). Ultimately, then, dynamical perturbations at mid-to-high latitudes can directly influence the variability of ozone and temperature (Sridharan et al, 2012;Nath and Sridharan, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Because of this effect, future tropical ozone levels even show further decline at the end of 21 st century compared to near present values. The slowing of photochemical ozone loss reactions caused by the cooling in the stratosphere (Barnett et al, 1975;Jonsson et al, 2004) contributes to a smaller degree to the overall TOC evolution (Zubov et al, 2013). Li et al (2009) showed that the BDC acceleration plays a crucial role in future ozone recovery and spatial distribution.…”
Section: Ozone Responsementioning
confidence: 99%
“…The tropospheric warming reaches a maximum of around 3 K in the tropical upper troposphere. Zubov et al (2013) showed that tropospheric warming is mainly caused by the surface warming due to increase of down-welling infrared radiation by GHG, enhanced by latent heat release in the middle troposphere. The temperature decrease in the stratosphere and mesosphere results from increased cooling rates of GHGs.…”
Section: Temperature Response 10mentioning
confidence: 99%